Survey study on energy use in UK homes during Covid-19. Issue 1 (27th December 2021) - Huebner, Gesche M.; Watson, Nicole E.; Direk, Kenan; McKenna, Eoghan; Webborn, Ellen; Hollick, Frances; Elam, Simon; Oreszczyn, Tadj
To contain the spread of Covid-19, governments across the world imposed partial or complete lockdowns. National energy demand decreased in periods of lockdowns; however, as people spent more time at home, residential energy use likely increased. This paper reports the results of a UK survey study ( N = 1016 participants) about their energy-use practices during the first lockdown in March 2020. The results indicated that self-reported heating behaviours did not substantially change during lockdown. Regarding appliance use, in particular the duration of usage for televisions and computing equipment has increased and has spread more over the day. Being less able to manage financially was correlated with a greater usage of the smart meter in-home display and a greater attempt to save energy was positively correlated with greater usage of the in-home display, though correlations were small. In summary, the results indicate that home energy-use behaviours, in particular around heating, did not change as much as might have been expected, which might at least partly be explained by the comparatively warm weather during the first lockdown. Corroborating the survey findings with actual energy data is the next essential step to understand findings in more detail. Policy relevance: Governments are developing policies to support the transition to net zero. Covid-19 has accelerated the transition in behaviours such as home working which may result in a 'new normal' energy behaviour and will need to be taken account when planning for net zero. Insights into the changes in behaviour during lockdown indicate it would be oversimplified to assume that electricity and gas use have increased in all homes because of a stay-at-home order. Self-reported heating did not change, whereas electrical appliance usage increased. The sample composition of the household is important for understanding the energy implications. In this study, about half the households did not spend more time at home during lockdown as judged on their work status. In-home displays may support energy saving behaviour, particularly for those doing less well financially. Hence, promoting their use should be a key consideration when installing smart meters.